Protective effect of honey against aluminium-induced erythrocyte osmotic fragility and hemoglobin denaturation : Honey protection against aluminium-induced erythrocytes alteration - Bellik, Yuva (Polish Journal of Natural Sciences, 2022)
The aim of the present study was to investigate the effects of honey supplementation on fluidity and morphology of human red blood cells (RBCs) treated with aluminium (Al). Human RBCs were pretreated separately with honey samples and ascorbic acid. Untreated RBCs suspensions served as control. Four different treatment groups were considered: untreated RBCs (negative control), aluminium treated RBCs (positive control), honey + aluminium treated RBCs and ascorbic acid + aluminium treated RBCs. Samples were then evaluated by simultaneous measurement of cellular turbidity and hemoglobin (Hb). The results showed that RBCs suspensions treated with honey samples, particularly honey 2 presented highest cell and Hb concentration values ​​compared to that of ascorbic acid and positive control, whereas, ascorbic acid exhibited a prooxidant effect on cell and Hb. The results of this study suggest that honey not only protect cell integrity but also prevent oxidative degradation of Hb. Therefore, the present study demonstrated a protective effect of honey against Al-induced changes on membrane fluidity in human erythrocytes.